HOW EXTENSIVE READING FACILITATES THE DEVELOPMENT OF WRITING FLUENCY IN SECOND LANGUAGE LEARNERS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
Extensive reading (ER) has become a widely used approach in second language (L2) learning because it exposes students to large quantities of comprehensible input. Although ER is frequently associated with gains in reading comprehension and vocabulary acquisition, growing research suggests that it also contributes significantly to writing development. This article examines how extensive reading supports writing fluency among L2 learners. The discussion highlights ER’s role in promoting lexical growth, supporting implicit grammar acquisition, strengthening discourse competence, enhancing cognitive processing, and boosting motivation. Together, these factors help learners produce more fluent, coherent, and confident written language.